# Chapter – 3: Trigonometric Functions

# Exercise 3.1

**1. Find the radian measures corresponding to the following degree measures:**

**(i) 25° (ii) – 47° 30′ (iii) 240° (iv) 520°**

**Solution: –**

(iv) 520°

**2. Find the degree measures corresponding to the following radian measures (Use π = 22/7)**

**(i) 11/16**

**(ii) -4**

**(iii) 5π/3**

**(iv) 7π/6**

**Solution: –**

(i) 11/16

Here π radian = 180°

(ii) -4

Here π radian = 180°

(iii) 5π/3

Here π radian = 180°

We get

= 300^{o}

(iv) 7π/6

Here π radian = 180°

We get

= 210^{o}

**3. A wheel makes 360 revolutions in one minute. Through how many radians does it turn in one second?**

**Solution: –**

It is given that

No. of revolutions made by the wheel in

1 minute = 360

1 second = 360/60 = 6

We know that

The wheel turns an angle of 2π radian in one complete revolution.

In 6 complete revolutions, it will turn an angle of 6 × 2π radian = 12 π radian

Therefore, in one second, the wheel turns an angle of 12π radian.

**4. Find the degree measure of the angle subtended at the centre of a circle of radius 100 cm by an arc of length 22 cm (Use π = 22/7).**

**Solution: –**

**5. In a circle of diameter 40 cm, the length of a chord is 20 cm. Find the length of minor arc of the chord.**

**Solution: –**

The dimensions of the circle are

Diameter = 40 cm

Radius = 40/2 = 20 cm

Consider AB be as the chord of the circle i.e. length = 20 cm

In ΔOAB,

Radius of circle = OA = OB = 20 cm

Similarly AB = 20 cm

Hence, ΔOAB is an equilateral triangle.

θ = 60° = π/3 radian

In a circle of radius *r* unit, if an arc of length *l* unit subtends an angle *θ* radian at the centre

We get θ = 1/r

Therefore, the length of the minor arc of the chord is 20π/3 cm.

**6. If in two circles, arcs of the same length subtend angles 60° and 75° at the centre, find the ratio of their radii.**

**Solution: –**

**7. Find the angle in radian though which a pendulum swings if its length is 75 cm and the tip describes an arc of length**

**(i) 10 cm (ii) 15 cm (iii) 21 cm**

**Solution: –**

In a circle of radius r unit, if an arc of length l unit subtends an angle θ radian at the centre, then θ = 1/r

We know that r = 75 cm

(i) l = 10 cm

So we get

θ = 10/75 radian

By further simplification

θ = 2/15 radian

(ii) l = 15 cm

So we get

θ = 15/75 radian

By further simplification

θ = 1/5 radian

(iii) l = 21 cm

So we get

θ = 21/75 radian

By further simplification

θ = 7/25 radian

# Exercise 3.2

**Find the values of other five trigonometric functions in Exercises 1 to 5.**

**1. cos x = -1/2, x lies in third quadrant.**

**Solution: –**

**2. sin x = 3/5, x lies in second quadrant.**

**Solution: –**

It is given that

sin x = 3/5

We can write it as

We know that

sin^{2} x + cos^{2} x = 1

We can write it as

cos^{2} x = 1 – sin^{2} x

**3. cot x = 3/4, x lies in third quadrant.**

**Solution: –**

It is given that

cot x = 3/4

We can write it as

We know that

1 + tan^{2} x = sec^{2} x

We can write it as

1 + (4/3)^{2} = sec^{2} x

Substituting the values

1 + 16/9 = sec^{2} x

cos^{2} x = 25/9

sec x = ± 5/3

Here x lies in the third quadrant so the value of sec x will be negative

sec x = – 5/3

We can write it as

**4. sec x = 13/5, x lies in fourth quadrant.**

**Solution: –**

It is given that

sec x = 13/5

We can write it as

We know that

sin^{2} x + cos^{2} x = 1

We can write it as

sin^{2} x = 1 – cos^{2} x

Substituting the values

sin^{2} x = 1 – (5/13)^{2}

sin^{2} x = 1 – 25/169 = 144/169

sin^{2} x = ± 12/13

Here x lies in the fourth quadrant so the value of sin x will be negative

sin x = – 12/13

We can write it as

**5. tan x = -5/12, x lies in second quadrant.**

**Solution: –**

It is given that

tan x = – 5/12

We can write it as

We know that

1 + tan^{2} x = sec^{2} x

We can write it as

1 + (-5/12)^{2} = sec^{2} x

Substituting the values

1 + 25/144 = sec^{2} x

sec^{2} x = 169/144

sec x = ± 13/12

Here x lies in the second quadrant so the value of sec x will be negative

sec x = – 13/12

We can write it as

**Find the values of the trigonometric functions in Exercises 6 to 10.**

**6. sin 765°**

**Solution: –**

We know that values of sin x repeat after an interval of 2π or 360°

So we get

By further calculation

= sin 45^{o}

= 1/ **√** 2

**7. cosec (–1410°)**

**Solution: –**

We know that values of cosec x repeat after an interval of 2π or 360°

So we get

By further calculation

= cosec 30^{o} = 2

**8. **

**Solution: –**

We know that values of tan x repeat after an interval of π or 180°

So we get

By further calculation

We get

= tan 60^{o}

= **√**3

**9. **

**Solution: –**

We know that values of sin x repeat after an interval of 2π or 360°

So we get

By further calculation

**10. **

**Solution: –**

We know that values of tan x repeat after an interval of π or 180°

So we get

By further calculation

# Exercise 3.3

**Prove that:**

**1.**

**Solution: –**

**2.**

**Solution: –**

Here

= 1/2 + 4/4

= 1/2 + 1

= 3/2

= RHS

**3.**

**Solution: –**

**4.**

**Solution: –**

**5. Find the value of:**

**(i) sin 75**^{o}

**(ii) tan 15**^{o}

**Solution: –**

(ii) tan 15°

It can be written as

= tan (45° – 30°)

Using formula

**Prove the following:**

**6.**

**Solution: –**

**7.**

**Solution: –**

**8.**

**Solution: –**

**9.**

**Solution: –**

Consider

It can be written as

= sin x cos x (tan x + cot x)

So we get

**10. sin ( n + 1)x sin (n + 2)x + cos (n + 1)x cos (n + 2)x = cos x**

**Solution: –**

LHS = sin (*n* + 1)*x* sin (*n* + 2)*x* + cos (*n* + 1)*x* cos (*n* + 2)*x*

**11.**

**Solution: –**

Consider

Using the formula

**12. sin**^{2}** 6 x – sin**

^{2}**4**

*x*= sin 2*x*sin 10*x***Solution: –**

**13. cos**^{2}** 2 x – cos**

^{2}**6**

*x*= sin 4*x*sin 8*x***Solution: –**

We get

= [2 cos 4x cos (-2x)] [-2 sin 4x sin (-2x)]

It can be written as

= [2 cos 4*x* cos 2*x*] [–2 sin 4*x *(–sin 2*x*)]

So we get

= (2 sin 4*x* cos 4*x*) (2 sin 2*x* cos 2*x*)

= sin 8x sin 4x

= RHS

**14. sin 2x + 2sin 4x + sin 6x = 4cos**^{2}** x sin 4x**

**Solution: –**

By further simplification

= 2 sin 4x cos (– 2x) + 2 sin 4x

It can be written as

= 2 sin 4x cos 2x + 2 sin 4x

Taking common terms

= 2 sin 4x (cos 2x + 1)

Using the formula

= 2 sin 4x (2 cos^{2} x – 1 + 1)

We get

= 2 sin 4x (2 cos^{2} x)

= 4cos^{2} x sin 4x

= R.H.S.

**15. cot 4 x (sin 5x + sin 3x) = cot x (sin 5x – sin 3x)**

**Solution: –**

Consider

LHS = cot 4x (sin 5x + sin 3x)

It can be written as

Using the formula

= 2 cos 4x cos x

Hence, LHS = RHS.

**16.**

**Solution: –**

Consider

Using the formula

**17.**

**Solution: –**

**18.**

**Solution: –**

**19.**

**Solution: –**

**20.**

**Solution: –**

**21.**

**Solution: –**

**22. cot x cot 2x – cot 2x cot 3x – cot 3x cot x = 1**

**Solution: –**

**23.**

**Solution: –**

Consider

LHS = tan 4x = tan 2(2x)

By using the formula

**24. cos 4 x = 1 – 8sin**

^{2 }

*x***cos**

^{2 }

*x***Solution: –**

Consider

LHS = cos 4x

We can write it as

= cos 2(2*x*)

Using the formula cos 2*A* = 1 – 2 sin^{2} *A*

= 1 – 2 sin^{2} 2*x*

Again, by using the formula sin2*A* = 2sin *A* cos *A*

= 1 – 2(2 sin* x *cos *x*) ^{2}

So we get

= 1 – 8 sin^{2}*x* cos^{2}*x*

= R.H.S.

**25. cos 6 x = 32 cos**

^{6}

*x*– 48 cos

^{4}

*x*+ 18 cos

^{2}

*x*– 1**Solution: –**

Consider

L.H.S. = cos 6*x*

It can be written as

= cos 3(2*x*)

Using the formula cos 3*A* = 4 cos^{3} *A* – 3 cos^{ }*A*

= 4 cos^{3} 2*x* – 3 cos^{ }2*x*

Again, by using formula cos 2*x* = 2 cos^{2} *x *– 1

= 4 [(2 cos^{2} *x *– 1)^{3} – 3 (2 cos^{2} *x* – 1)

By further simplification

= 4 [(2 cos^{2} *x*) ^{3} – (1)^{3} – 3 (2 cos^{2} *x*) ^{2} + 3 (2 cos^{2} *x*)] – 6cos^{2} *x* + 3

We get

= 4 [8cos^{6}*x* – 1 – 12 cos^{4}*x* + 6 cos^{2}*x*] – 6 cos^{2}*x* + 3

By multiplication

= 32 cos^{6}*x* – 4 – 48 cos^{4}*x* + 24 cos^{2} *x* – 6 cos^{2}*x* + 3

On further calculation

= 32 cos^{6}*x *– 48 cos^{4}*x* + 18 cos^{2}*x* – 1

= R.H.S.

# Exercise 3.4

**Find the principal and general solutions of the following equations:**

**1. tan x = √3**

**Solution: –**

**2. sec x = 2**

**Solution: –**

**3. cot x = – √3**

**Solution: –**

**4. cosec x = – 2**

**Solution: –**

**Find the general solution for each of the following equations:**

**5. cos 4x = cos 2x**

**Solution: –**

**6. cos 3x + cos x – cos 2x = 0**

**Solution: –**

**7. sin 2x + cos x = 0**

**Solution: –**

It is given that

sin 2x + cos x = 0

We can write it as

2 sin x cos x + cos x = 0

cos x (2 sin x + 1) = 0

cos x = 0 or 2 sin x + 1 = 0

Let cos x = 0

**8. sec**^{2}** 2x = 1 – tan 2x**

**Solution: –**

It is given that

sec^{2} 2x = 1 – tan 2x

We can write it as

1 + tan^{2} 2x = 1 – tan 2x

tan^{2} 2x + tan 2x = 0

Taking common terms

tan 2x (tan 2x + 1) = 0

Here

tan 2x = 0 or tan 2x + 1 = 0

If tan 2x = 0

tan 2x = tan 0

We get

2x = nπ + 0, where n ∈ Z

x = nπ/2, where n ∈ Z

tan 2x + 1 = 0

We can write it as

tan 2x = – 1

So we get

Here

2x = nπ + 3π/4, where n ∈ Z

x = nπ/2 + 3π/8, where n ∈ Z

Hence, the general solution is nπ/2 or nπ/2 + 3π/8, n ∈ Z.

**9. sin x + sin 3x + sin 5x = 0**

**Solution: –**

It is given that

sin x + sin 3x + sin 5x = 0

We can write it as

(sin x + sin 5x) + sin 3x = 0

Using the formula

By further calculation

2 sin 3x cos (-2x) + sin 3x = 0

It can be written as

2 sin 3x cos 2x + sin 3x = 0

By taking out the common terms

sin 3x (2 cos 2x + 1) = 0

Here

sin 3x = 0 or 2 cos 2x + 1 = 0

If sin 3x = 0

3x = nπ, where n ∈ Z

We get

x = nπ/3, where n ∈ Z

If 2 cos 2x + 1 = 0

cos 2x = – 1/2

By further simplification

= – cos π/3

= cos (π – π/3)

So we get

cos 2x = cos 2π/3

Here

##### Tags In

### Related Posts

### Leave a Reply Cancel reply

**Error:** Contact form not found.